Respect and take care of things - Meiners, Cheri J., 1957-; Johnson, Meredith (Minneapolis, MN : Free Spirit, 2004)
A young girl discovers the values of respect, responsibility, and stewardship as she learns to take care of herself and the things around her, put things in their place, and respect other peoples' belongings.
Book Links (A.L.A.)
2.0
K-3
K-3
Keywords: Caring -- Juvenile literature; Respect -- Juvenile literature; Caring; Respect; Caring; Conduct of life; Respect